Alternativa de tratamiento de aguas provenientes de piscinas termales de Paipa para el posterior vertimiento en el Río Chicamocha (2021)
In the municipality of Paipa, located in the department of Boyacá, there is a tourist complex that focuses its activities on the use of hot springs. The generated discharges are directed towards the Chicamocha River, which satisfies a great demand for water needed for human and domestic, agricultural, livestock, recreational and industrial consumption. For this reason, this project aims to propose a conceptual design for the treatment of water from thermal pools that favors the reduction of sulfate and chloride ions. This proposal is made based on the current state of the discharge determined by means of a specific type of sampling protocol, in which chemical analyses of the parameters of interest were carried out. These showed that the concentration of chloride ions exceeds 2305.5 %, where the established regulation of a minimum value is 250 mg Cl- / L.